The Preference Selection Index Method in Determining the Location of Used Laptop Marketing - Hafni Sahir, Syafrida; Afriani, Joli; Ginting, Garuda; Fachri, Barany; Siregar, Dodi; Simbolon, Ramadona; Lindawati, L; Syarizal, Muhammad; Mesran, M; Fadlina, F; Simarmata, Janner (International Journal of Engineering and Technology, 2026)
The rapid development of laptops has caused users to renew their laptops. This has resulted in many laptops that are still suitable for use, and are still in great demand by the public, even though the laptop is not new anymore. In order for the sale of used laptops to be right on target for those in need, of course, in this case, the marketing area selection must be right. The choice of marketing area is an important thing in sales activities. Many factors are needed in the selection of a marketing area, including rental prices, area, visitors, distance. In order for the decision to choose this marketing area to be effective, a decision support system is needed that can provide the right decision in processing alternatives. In this study, the author uses the Preference Selection Index (PSI) method. It is expected that the PSI method is able to process alternatives according to the specified criteria.
Keywords: Marketing Location; Used Laptop; PSI; Preference Selection Index; DSS